Different Approaches to Unveil Biomolecule Configurations and Their Mutual Interactions. (22nd January 2021) - Benedetti, R.; Bajardi, F.; Capozziello, S.; Carafa, V.; Conte, M.; Del Sorbo, M. R.; Nebbioso, A.; Singh, M.; Stunnenberg, H. G.; Valadan, M.; Altucci, L.; Altucci, C.
Abstract: A novel technique was demonstrated that overcomes important drawbacks to crosslink cells by irradiation with ultrashort ultraviolet laser pulses (L-crosslinking). To use this technique coupled to Chromatin ImmunoPrecipitation (ChIP) in a high throughput context, a prescreening fast method needs to be implemented to set up suitable irradiation conditions of the cell sample for efficient L-crosslinking with no final and long ChIP analysis. Here a fast method is reported where living human cells have been first transfected with a vector coding for Estrogen Receptor α (ERα), linked to Green Florescent protein (ERα-GFP), so that the well-known interaction between the Estrogen Receptor Elements (ERE) region of the cell DNA and the ERα protein can be detected by studying the fluorometric response of the irradiated cells. The damage induced to cells by ultraviolet irradiation is characterized by looking at the DNA integrity, protein stability, and cellular viability. A second novel approach is presented to analyze or re-visit DNA and RNA sequences and their molecular configurations. This approach is based on methods derived from Chern-Simons super-gravity adapted to describe mutations in DNA/RNA strings, as well as interactions between nucleic acids. As a preliminary case, we analyze the KRAS human gene sequence and some of its mutations. Interestingly, our model shows how the Chern-Simons currents are able to characterize the mutations within a sequence, in particular giving a quantitative indication of the mutation likelihood.